Digital transformation and innovation management: A systematic literature review - Naldi, Syafri; Gusty, Ryndian; Saqdiah, Fatma (PT Aksara Indo Rajawali, 2025)
Digital transformation has become a strategic driver that significantly influences organizational sustainability through changes in technology, business models, and innovation management. This study aims to examine the relationship between digital transformation and innovation management by employing a Systematic Literature Review (SLR) method. A total of 20 articles published between 2020 and 2025 were analyzed to identify trends, thematic focuses, and methodological gaps. The findings reveal seven dominant themes: digital business model innovation, digital strategy and organizational effectiveness, data-driven innovation and entrepreneurship, innovation management systems and tools, open innovation and ecosystems, entrepreneurship and digital innovation, and agile innovation and organizational adaptability. The study highlights that the literature remains dominated by conceptual and review-based research, with a limited number of empirical and quantitative analyses. This indicates the need for further research that explores practical applications and organizational contexts. The conclusion emphasizes the importance of integrating digital strategies with innovation management to achieve sustainable competitive advantage. The practical implication suggests that organizations should strengthen their innovation culture, organizational agility, and technology adoption. The theoretical implication contributes by mapping thematic trends and identifying gaps that may serve as a foundation for future research and theory development.